Solely MRI-Guided Cardiac Catheterization for Assessment of Pulmonary Hypertension in a Pregnant Lady with Undiagnosed Congenital Heart Disease - Aphrodite Tzifa; Ioannis Polymerou; Dimitra Loggitsi (Case Reports in Cardiology)
Pregnancy in women with complex congenital heart disease (CHD) can be poorly tolerated. Amongst pregnant women with CHD and pulmonary hypertension (PH), the mortality rate can be as high as 30%. Cardiac catheterization procedures for assessment of haemodynamics and pulmonary vascular resistance (PVR) are often required in this patient population for risk stratification. However, during the first few weeks of pregnancy, this should better be avoided due to the known adverse effects of the ionizing radiation to the immature fetus. In this setting, a solely MRI-guided catheterization may present as a better alternative.